The Influence of Income, Value Added Tax Increase, and Cigarette Excise Tax Increase on Conventional Cigarette Consumption - Intan Permata Sari; Apip Apip (Tax Accounting Applied Journal, 2025)
This study aims to examine the effect of income, Value Added Tax (VAT) increase, and cigarette excise tax increase on conventional cigarette consumption among individuals aged 20–30 years in Cirebon City. The research employed a descriptive quantitative method using a questionnaire distributed to 100 randomly selected respondents. Data were analyzed using multiple linear regression with the help of SPSS software. The results indicate that income (X₁) and VAT increase (X₂) have a significant effect on cigarette consumption with significance values of 0.004 and 0.006, respectively (<0.05). However, the excise tax increase (X₃) showed no significant effect (sig. 0.230 > 0.05). The coefficient of determination (R²) is 0.223, indicating that 22.3% of the variation in cigarette consumption can be explained by the three independent variables, while the remaining 77.7% is influenced by other factors not examined in this study.